МӘҢГИЛЕСТИРИЛИЎИ ТИЙИС МУҚАДДЕС МӘДЕНИЙ МИЙРАСЛАР (тарийхы, ҳәзирги ҳалаты, келешек тәғдири мәселелери) - Алламбергенов, К.; Эгамкулова, Г.М. (SCIENCE and SOCIETY, 2021)
The article deals with some valuable recommendations and necessary solutious of karakalpak bakshis’ (folk songs), art of guttural singing, national heritages, origin of this art, traditions which continious from long times, present conditions, musical instruments and oratory art, school of tutors.
Keywords: independence; national values; national heritage; word skill; bakshi; jiraw; genealogy of bakshi and jiraw; Korkit ata; jir; qobiz; Soppasli Sipira jiraw and karakalpak jiraw school; roots of Karakalpak jiraw school; foundations of karakalpak bakshi schools; Akimbet bakshi school Musa and Suyew bakshi; karakalpak bakshi ahd jiraws of XX century